Origin of photoluminescence from colloidal gallium phosphide nanocrystals synthesized via a hot-injection method. Issue 4 (9th December 2014) - Kim, Sungwoo; Lee, Kangha; Kim, Sejin; Kwon, O.-Pil; Heo, Jin Hyuk; Im, Sang Hyuk; Jeong, Sohee; Lee, Doh C.; Kim, Sang-Wook
Abstract : The emission and excitation spectra of the GaP NCs indicate that two transitions, near the direct and indirect bandgaps of bulk GaP, are responsible for the luminescence. Abstract : In this work, photoluminescence from colloidal GaP nanocrystals (NCs) synthesized via a hot-injection method is observed and analyzed. The emission and excitation spectra of the GaP NCs indicate that two transitions, near the direct and indirect bandgaps of bulk GaP, are responsible for the luminescence.